Final instar larva of Franciscagrion longispinum Machado & Bedê, 2015 (Odonata: Coenagrionidae), an endemic species from the springs of the São Francisco river - Cezário, Rodrigo Roucourt; Vilela, Diogo Silva; Guillermo-Ferreira, Rhainer (Zootaxa, 2019)
Franciscagrion longispinum Machado & Bedê larvae were collected in the São Francisco river historical springs at the Serra da Canastra National Park, Brazil. Here, we describe and illustrate the final instar larvae of this rare and endemic species.